VD_FINDINFO HC / 2024 / 4 vom 19. Januar 2024 - VD Tribunal cantonal (2024)
MESURE PROVISIONNELLE, DIVORCE, MODIFICATION DES CIRCONSTANCES, CONCUBINAGE, OBLIGATION D'ENTRETIEN | 179 al. 1 CC, 179 CC, 276 al. 1 CPC (CH), 318 al. 3 CPC (CH)